Electric Vehicles Are a Platform Business: What Firms Need to Know. (August 2022) - Anderson, Edward G.; Bhargava, Hemant K.; Boehm, Jonas; Parker, Geoffrey
Many of the most successful firms—such as Alibaba, Google, and Uber—operate platforms. Electric vehicles (EVs) are platform goods as well because value comes from the vehicle plus complementary providers. Gasoline vehicles are also platform goods, but managers in the industry can ignore that because the refueling network is mature. However, temporal and structural differences in network effects for electric vehicles make it crucial for EV firms to incorporate platform strategies. This article explains these differences and outlines the key platform strategy decisions that EV firms need to make, including platform network coordination, launch, and openness.